2017
DOI: 10.1177/1535370217716424
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of miR29a improves impaired post-ischemic angiogenesis in hyperglycemia

Abstract: Individuals with diabetes mellitus suffer from impaired angiogenesis and this contributes to poorer peripheral arterial disease outcomes. In experimental peripheral arterial disease, angiogenesis and perfusion recovery are impaired in mice with diabetes. We recently showed that a disintegrin and metalloproteinase domain-containing protein 12 (ADAM12) is upregulated in ischemic endothelial cells and plays a key role in post-ischemic angiogenesis and perfusion recovery following experimental peripheral arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 34 publications
1
56
0
Order By: Relevance
“…improved impaired post-ischemic angiogenesis in diabetes [17]. In the present study, miR-548j-5p was observed to facilitate migration and tube formation in EPCs, indicating that miR-548j-5p may contribute to angiogenesis in PAD by regulating the angiogenic activities of EPCs.…”
Section: Discussionsupporting
confidence: 61%
“…improved impaired post-ischemic angiogenesis in diabetes [17]. In the present study, miR-548j-5p was observed to facilitate migration and tube formation in EPCs, indicating that miR-548j-5p may contribute to angiogenesis in PAD by regulating the angiogenic activities of EPCs.…”
Section: Discussionsupporting
confidence: 61%
“…Male C57BL6 mice (8 weeks of age) were given multiple low-dose STZ (MLD-STZ), intraperitoneal doses of 40 mg/kg of STZ in citrate buffer (pH 4.5) for 5 days consecutively. The level of hyperglycemia in the experimental and control groups of mice were determined by measuring hemoglobin A1C (PTS Diagnostics, IN, U.S.A) and fast blood glucose as previously described [ 12 ], and the groups were found to have identical levels of hemoglobin A1C and fast blood glucose. Three weeks after diabetes induction, all nondiabetic and diabetic mice received unilateral hindlimb artery ligation and excision as described previously [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The level of hyperglycemia in the experimental and control groups of mice were determined by measuring hemoglobin A1C (PTS Diagnostics, IN, U.S.A) and fast blood glucose as previously described [ 12 ], and the groups were found to have identical levels of hemoglobin A1C and fast blood glucose. Three weeks after diabetes induction, all nondiabetic and diabetic mice received unilateral hindlimb artery ligation and excision as described previously [ 12 , 13 ]. To understand the function of miR-133a on perfusion recovery, miR-133a was knocked down using cholesterol-conjugated miR-133a antagomir retro-orbitally at a dose of 8 mg/kg body weight in STZ-induced diabetic mice day 1 before HLI; on the other hand, miR-133a was overexpressed in the ischemic limb by using an intramuscular injection of pCMV-miR-133a followed by electroporation day 3 before HLI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the increased expression of HBP1, a target gene of miRNA-29a, mediates resisting hypoxic damage by miR-29a. Chen et al 14 demonstrated that miRNA-29a upregulates ADAM metallopeptidase domain 12 (ADAM12) in ischemic endothelial cells, which is impaired in hyperglycemia. 12 Studies have shown that the expression of miRNA-29a decreased significantly in human amniotic mesenchymal stem cells (hAMSCs) exposed to serum-free and hypoxi, and miRNA-29a knockdown resulted in decreased apoptosis of hAMSCs by increasing myeloid cell leukemia-1 (MCL-1).…”
mentioning
confidence: 99%